AB0361 EFFICACY AND SAFETY OF BARICITINIB (BARI) IN RHEUMATOID ARTHRITIS(RA): CLINICAL AND ULTRASOUND EVALUATION IN REAL LIFE. (2nd June 2020) - Tesei, G.; Bruni, C.; Cometi, L.; Nacci, F.; Capassoni, M.; Terenzi, R.; Tofani, L.; Bartoli, F.; Fiori, G.; Matucci-Cerinic, M.
Abstract : Background: Remission or low disease activity (LDA) are the ultimate goals of both conventional synthetic (csDMARD), target synthetic and biologic disease-modifying anti-rheumatic drugs (bDMARD) in treating RA. Janus Kinase (JAK) inhibitors are nowadays part of tsDMARDs, with BARI as an oral selective JAK1-2 inhibitor. Ultrasound (US) is a valuable imaging tool for detecting inflammatory joint changes and monitoring RA patients. The US7 score (US7) is a semiquantitative score including grayscale (GS) and power Doppler (PD) measurements of synovitis and tenosynovitis in 7 joints of the clinically dominant hand and foot. Objectives: to evaluate real life efficacy and safety of BARI 4 mg in RA patients using clinical, clinimetric and US evaluation. Methods: adult RA patients starting BARI were eligible. DAS28ESR, CDAI, SDAI, painVAS, HAQ, COCHIN, laboratory parameters and US7 were performed/collected at baseline (BL) and after 3 and 6 months. Adverse events (AE) and concomitant medications were recorded. Responder/non responder status was determined using DAS28ESR improvement according to the EULAR Response Criteria at 3 months. Moreover, SDAI clinical remission or LDA (remission: SDAI≤3, 3; LDA:3, 3<SDAI≤11) were calculated at 3 and 6 months. Results: 43 patients (12 csDMARD and 31 bDMARD failure) were enrolled, with 30 patients starting BARI in combination with a csDMARDs. BL painVAS was 68±23mm and disease activity was moderate to severe according to DAS28VES, CDAI and SDAI. BARI determined a significant improvement of every disease activity composite score and US7 components, except tendon PD; steroid daily dosage was significantly reduced. 28 patients were considered Responders at 3 months: responders used to have higher disease activity levels and synovitis scores at baseline. Interestingly, painVAS and steroid dosage significantly decreased both in responders and non-responders, achieving similar value at 6 months. Non-responders showed both synovial and tendon involvement relapse at 6 months, with significantly higher PD score compared to responders. Remission was reached by 12, 8% patients at 3 months and 21, 6% at 6 months, while LDA patients were respectively 53, 8% and 51, 3%; combination with csDMARD was the only factor positively associated with remission/LDA at 3 months. The percentage of dropped-out patients due to AE was aligned with literature data (5% in 6 months) whereas the percentage of Herpes Zoster Virus (HZV) infections was higher (4, 6% in 6 months in our population vs 4, 3% in 1 year in RCTs). Corticosteroid dosage was directly associated with AE development at 6 months. Conclusion: Real life data confirmed BARI RCTs efficacy and safety data. Non responders showed both synovial and tendon PD disease relapse, despite painVAS and steroid reduction were comparable to responders. In our population, HZV infection prevalence was higher than in RCTs and corticosteroid dosage was positively associated with AE development at 6 months. Disclosure of Interests: Giulia Tesei: None declared, Cosimo Bruni Speakers bureau: Actelion, Eli Lilly, Laura Cometi: None declared, Francesca Nacci: None declared, Marco Capassoni: None declared, Riccardo Terenzi: None declared, Lorenzo Tofani: None declared, Francesca Bartoli: None declared, Ginevra Fiori: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim